Piglets' acute responses to procaine-based local anesthetic injection and surgical castration: Effects of two volumes of anesthetic - Coutant, Mathilde; Malmkvist, Jens; Kaiser, Marianne; Foldager, Leslie; Herskin, Mette S. (Frontiers in Pain Research, 2022)
Surgical castration of piglets is painful, but practiced routinely in commercial pig production. Procaine-based local anesthetics are used to mitigate piglet pain during castration in some countries. Yet, effects of the volume of anesthetic injected remain under-studied. The volume of drug administered may modulate the pain mitigating effect via variation in intra-testicular pressure at injection, potentially leading to pain or discomfort, as well as variation in the dose of active ingredient administered. The present study investigated the effects of injection with two volumes of a procaine-based local anesthetic, 0.3 vs. 0.5 mL per testis, on acute responses of 3–4 day old piglets. A total of 290 piglets were divided into 5 treatment groups: castration without anesthesia, castration after intra-testicular injection of 0.5 or 0.3 mL of drug per testis, and sham handling with one or two stays in a castration bench. Acute responses to drug injection, castration and sham handling were evaluated based on quantification of intra-procedural vocalizations and foreleg movements, as well as saliva cortisol concentrations before and after castration. Regardless of the volume, injection of anesthetic as well as castration led to significantly stronger responses than sham handling. Responses to the two drug volumes did not differ significantly, and responses to castration following injection of 0.3 mL did not differ from piglets castrated without anesthesia. All treatments, including sham handling, led to a significant increase in saliva cortisol, and no difference was found between anesthesia treatments and sham handling. Overall, the results suggested that injection of 0.5 mL led to better pain mitigation at castration compared to injection of 0.3 mL, but even when the local anesthetic was used, the combined procedures of injection and castration led to intra-procedural signs of pain and stress.